PENINGKATAN KAPASITAS DAN PELATIHAN PEREMPUAN DALAM PENGEMBANGAN DESA WISATA RINTISAN: STUDI KASUS DESA DIMEMBE SEBAGAI PENDUKUNG DESTINASI PARIWISATA SUPER PRIORITAS LIKUPANG - Walansendow, Agustinus; Lagarense, Jeskrispen (UPT Penelitian Sekolah Tinggi Ilmu Pariwisata Manado, 2025)
The development of Super Priority Destinations (DSP) in Indonesia requires comprehensive support from surrounding villages. Dimembe Village, located 15 km from the Likupang Special Economic Zone, has significant potential as a pioneer tourism village, but faces challenges in women's capacity for tourism development. This study aims to analyze the effectiveness of women's capacity building and training programs in preparing Dimembe Village as a pioneer tourism village supporting the Likupang Super Priority Destination. This participatory action research was carried out for 9 months (2024) involving 115 women from various productive groups in Dimembe Village. This study uses a mixed method approach that combines quantitative assessment and qualitative participatory observation. Interventions include product development training, business management capacity building, digital marketing skills, and tourism service standards. This program has succeeded in increasing women's participation in the tourism economy by 45%, with an increase in average income by 35%. Key achievements include: (1) Development of 15 new handicraft products that meet tourism market standards; (2) Establishment of 2 productive business groups with 30 active members; (3) Establishment of 5 standardized homestays; (4) Creation of 3 integrated cultural tourism packages; (5) Implementation of a digital marketing system that reaches 90% of participants. Participatory capacity building programs are effective in increasing the role of women in the development of pioneer tourism villages. An integrated approach that combines product development, business management, and digital literacy creates sustainable economic opportunities while preserving local cultural values